Application of Cooperative Learning Learning Snowball Throwing Model to Improve The Results of History Learning For Learners - Lusia Rini Idriastuti (Green Publisher Indonesia, 2021)
This study aims to improve student learning outcomes by contextual learning using the Snowball throwing model of history learning to students in class XII IPS 2 at SMA Negeri 3 Magelang in the Even Semester of the 2019/2020 academic year. The method used is by using Classroom Action Research (CAR). This research uses 2 cycles which include planning, implementation, observation, and reflection activities. In this study the data sources come from observations, document texts, questionnaires, photos and learning outcomes test. The validity of the data in this study uses triangulation, which consists of triangulation of data sources and methods, while the data analysis uses quantitative and descriptive quantitative analysis. The results of this study indicate that the application of the Snowball Throwing method which was developed with discussion models, oral question and answer can improve student learning outcomes. The Snowball throwing learning model was proven to be able to improve student learning outcomes. Constraints faced are using a long time, not all material can be absorbed by students, conditions and situations in using the Snowball Throwing method must be conducive.